2020
DOI: 10.3390/biomedicines8050119
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Hordenine as a Potential Inhibitor of Pyruvate Dehydrogenase Kinase 3: Implication in Lung Cancer Therapy

Abstract: Design and development of potential pyruvate dehydrogenase kinase 3 (PDK3) inhibitors have gained attention because of their possible therapeutic uses in lung cancer therapy. In the present study, the binding affinity of naturally occurring alkaloids, hordenine, vincamine, tryptamine, cinchonine, and colcemid was measured with PDK3. The molecular docking and fluorescence binding studies suggested that all these compounds show a considerable binding affinity for PDK3. Among them, the affinity of hordenine to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 69 publications
0
60
0
Order By: Relevance
“…Several small molecules, such as radicicol, M77976, and hordenine, are known to be PDK inhibitors that interfere with ATP binding [ 18 , 33 , 34 ]. Recently, hordenine, an alkaloid isolated from marine algae, was reported to be a PDK3 inhibitor possibly interacting with the ATP binding site [ 35 ]. The ATP binding region of the PDKs, which is located at the end of the C-terminal domain, is a very conserved domain comprising four-strand mixed β-sheets and three α-helices [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small molecules, such as radicicol, M77976, and hordenine, are known to be PDK inhibitors that interfere with ATP binding [ 18 , 33 , 34 ]. Recently, hordenine, an alkaloid isolated from marine algae, was reported to be a PDK3 inhibitor possibly interacting with the ATP binding site [ 35 ]. The ATP binding region of the PDKs, which is located at the end of the C-terminal domain, is a very conserved domain comprising four-strand mixed β-sheets and three α-helices [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the anticancer efficiency of IQ is higher than that of JX06 and AZD7545 in A549 cells. The GI 50 concentrations of hordenine, a small molecule PDK inhibitor that interferes with ATP binding, were reported to be 14.95 μM in A549 cells following 48-h treatment [ 35 ]. The derivatives of radicicol and M77976 showed potent cytotoxic activities on several cancer cell lines [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of these plant-based products has been explored in terms of their kinase targeting capabilities. 23 27 Around 80% of the population still relies on plant-derived formulations to manage different medical issues. 19 In recent years, there is a switch in the screening and discovery of natural products as potential kinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…These new and old inhibitors provide many new ideas and strategies aiming at targeting PDK for anti-cancer therapy and treatments for other metabolic diseases. Human gallbladder cancer [74] Breast cancer [113] Ovarian cancer [114] Hypoxic tumors [115] Neck squamous cell carcinoma [75] Multiple myeloma [116] Colorectal Cancer [117] Glioblastoma [118] PDK2 Ovarian cancer [119] Glioblastoma [120] Type 2 diabetes [121] Lung cancer [84] PDK3 Colon cancer [87,88] X-linked Charcot-Marie-Tooth neuropathy [122] Lung Cancer [123] PDK4 Type 2 diabetes [121,124,125] Hemochromatosis [126] Glucocorticoid excess; e.g., Cushing syndrome [5,127] Cardiac hypertrophy [128] Statin induced myopathy [129] Ovarian cancer [119] Anoikis and tumor metastasis [10] Vascular Calcification [68,69,130,131] Colon cancer [91,132] Nonalcoholic steatohepatitis [133] Prostate cancer [134] Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20204402/906158/bsr-2020-4402.pdf by guest on 29 March 2021…”
Section: Pdks Inhibitorsmentioning
confidence: 99%